On Generalized Statistical Convergence of Order of Difference Sequences - Mikail Et; Hıfsı Altınok; Yavuz Altın (Journal of Function Spaces and Applications)
We introduce the concept of statistical convergence of order of difference sequences, and we give some relations between the set of statistical convergence of order of difference sequences and strong -summability of order . Furthermore some relations between the spaces and are examined.